In Search of the Inner Mind: Old English Gescead and Other Lexemes for Human Cognition in King Alfred’s Boethius - Šileikytė, Rūta (Kalbotyra, 2004)
The article discusses the Old English terminology for human cognition in King Alfred’s translation of Boethius’ Consolation of Philosophy. The Old English lexemes for human mind, soul, and intellect are investigated with respect to their immediate context in the vernacular. as well as the broader tradition of medieval Latin terminology that underpins the Anglo-Saxon rendering of the treatise. The study argues that although no exact relationship can be established between the vernacular and the corresponding Latin set of terms, the Old English rendering does succeed in conveying the essential structures of Boethius’thought, thus transmitting Late Antique heritage to the ninth-century philosophical discourse of Anglo-Saxon England.